Detection of gastrointestinal parasites in ferrets (Mustela putorius furo) by coprological analysis - Troncoso, I. (2019)
The aim of this study was to determine the presence of zoonotic gastrointestinal parasites by coprological examination in ferrets (Mustela putorius furo) reared as pets and the role of sex and age. The faeces of 30 ferrets were analysed, 16 [53.3%] from pet stores and 14 [46.7%] from homes in the city of Santiago and Concepción, Chile. Burrows' coprological technique was used for the diagnosis, which allows detecting eggs of protozoan helminths, cysts and trophozoites Three samples (10%) tested positive for protozoa, one for Entamoeba coli, in a 6 month old male from a pet store, and two for Endolimax nana in a 3-month-old female and a 2-year-old male from private homes. This would be the first record for the two species of protozoa commensals in ferrets in Chile, which were probably acquired by the close contact of mustelids with humans.